Tourism Without Barriers: A Virtual Reality Platform for an Immersive, Inclusive, and Accessible Experience - Silva Abanto, Roger; Julcamoro Cotrina, Johan Javier; Rodriguez Peregrino, Luna Aracely; Rojas Pajares, Ivan; Sanchez Tirado, Walter Adrian; Teran Cholan, Miguel Angel (LACCEI, 2025)
Abstrac: The purpose of this project is to develop an interactive web platform called Tourism Without Barriers, aimed at providing inclusive access to regional tourism through the use of virtual reality technologies. The initiative arose in response to the need to bring Cajamarca’s cultural and natural heritage closer to people with disabilities or reduced mobility, who face physical barriers to participating in conventional tourism activities. The platform allows virtual tours of iconic destinations such as Jaén, San Marcos, and Cajamarca through immersive videos in SBS format, accompanied by accessible and multilingual navigation controls. Low-cost tools such as HTML5, FFmpeg, and Netlify were used, prioritizing usability, adaptability, and user autonomy. The methodology included a pilot test, feedback collection, functional adjustments, and design validation. The results show that the experience was positively rated by users, highlighting its accessibility, ease of use, and immersive capabilities. It is concluded that virtual reality, applied with an inclusive and educational approach, represents an effective and replicable alternative for promoting barrier-free tourism in similar contexts.